Sustainable Municipal Solid Waste Management with Zero Waste Approach - Oztas, Serpil; Bektas, Nihal (Springer International Publishing Ag, 2022)
The world's resources are limited and threatened by numerous factors such as population growth, climate change and waste and pollution from municipal and industrial processes. Human beings use technologies and improvements to expand economic growth and enhance their lives. However, it is essential to be used these developments in a clever or sustainable way so that future generations can use the same resources. Also, great loss and collapse of biodiversity and ecosystems with irreversible consequences which leads to a severe depletion of resources and environment for humanity and industry. Therefore, sustainability is an important perception and Sustainable Waste management does not only generate local impacts but also would minimize environmental burden of the plant earth. Municipal SolidWaste (MSW) is recognized as a public service and should be managed using methods supported by different technologies within the framework of the rules determined by legal requirements. The aim of this presentation to show the importance of sustainable waste management options for our society through the Zero Waste Regulation since it can reduce or eliminate harmful environmental effects through proper initial municipal waste management applications.
5th International Conference on Natural Resources and Sustainable Environmental Management -- NOV, 2021 -- Near E Univ, Nicosia, CYPRUS
Keywords: Sustainability; Waste management; Circular economy; Zero waste